The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1590/1980-5373-mr-2015-0516
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Metal Acetylacetonates on the Photooxidative Destruction of High Density Polyethylene

Abstract: The process of photooxidative destruction of high density polyethylene films containing different organic complexes of polyvalent metals as pro-oxidant additives after UV-irradiation was studied. During exposure to UV-irradiation, the more significant changes in the mechanical and thermal properties were detected for the foils containing pro-oxidant additives compared to initial high density polyethylene. This indicated for the higher degree of oxidation in these samples and confirmed the effectiveness of thеs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
1
0
1
Order By: Relevance
“…Table 1 presents the overall relative reactivity of different metal compounds in different media, phases, and conditions (light or the absence of light). It is worth noting that, as revealed by Kiryakova et al [56], PE has the highest extent of photo-oxidation corresponding to manganese(II) and cobalt(III) acetylacetonates, whereas, for PP, vanady(II) and iron(III) acetylacetonates had the most pronounced effect.…”
Section: Comparison Of Metals As Oxidation Catalyzers: Uv Accelerationmentioning
confidence: 84%
“…Table 1 presents the overall relative reactivity of different metal compounds in different media, phases, and conditions (light or the absence of light). It is worth noting that, as revealed by Kiryakova et al [56], PE has the highest extent of photo-oxidation corresponding to manganese(II) and cobalt(III) acetylacetonates, whereas, for PP, vanady(II) and iron(III) acetylacetonates had the most pronounced effect.…”
Section: Comparison Of Metals As Oxidation Catalyzers: Uv Accelerationmentioning
confidence: 84%
“…Titanium acetylacetonate restricted losses in weight and tensile strength of thin radiata pine (Pinus radiata D. Don) veneers exposed to natural weathering [9], but the effectiveness of other acetylacetonates at photostabilizing 2 of 13 wood has not been tested. In contrast, much more research has been carried out on the photoprotection of polymers with different metal acetylacetonates [12,13]. These studies have found that the effectiveness of metal acetylacetonates as photostabilizers for polymers varies with type of acetylacetonate and polymer species.…”
Section: Introductionmentioning
confidence: 99%
“…Na literatura, há estudos que relatam o comportamento da degradação do polietileno com aditivos oxibiodegradantes que possuem metais pesados na sua composição como, por exemplo, Manganês (ABRUSCI et al, 2013;KIRYAKOVA et al, 2016;BENÍTEZ et al, 2013;KONDURI et al, 2011;MARYUDI et al, 2012;MARYUDI et al, 2013;JAKUBOWICZ et al, 2011), Cobalto (ABRUSCI et al, 2013KIRYAKOVA et al, 2016;SAMAL et al, 2014;KONDURI et al, 2011;FOCKE et al, 2011), Titânio (YANG et al, 2006MANANGAN et al, 2010;KONDURI et al, 2011), Cobre (FOCKE et al, 2011, entre outros.…”
Section: Introductionunclassified